A method for studying lipid adsorption to silicone hydrogel contact lenses. Issue 8 (14th September 2021) - Masoudi, Simin; Willcox, Mark
Abstract: The aim of this study was to develop an experimental methodology to measure lipid deposition with contact lenses. Contact lenses were incubated in a lipid solution. The amount and types of adsorbed lipids were assessed using mass spectrometry and confocal microscopy. The recovery of lipids from lenses varied with lipid and lens type. Most non-polar and polar lipids were desorbed from lenses during the first 5 min of extraction. Fluorescently labelled phosphatidylcholine bound within the matrix of Senofilcon A lenses but to the surface of Lotrafilcon B lenses, whereas fluorescently labelled cholesteryl ester was found throughout both lenses. The efficacy of extraction of lipids from contact lenses varies for different lipid classes and different lens materials. Differences in the amount and time of lipid desorption probably resulted from the strength of the bond between lipid and lens polymer and the depth of adsorption of lipid in the polymer.